Pulmonary involvement in diffuse cutaneous systemic sclerosis: broncheoalveolar fluid granulocytosis predicts progression of fibrosing alveolitis. Issue 10 (1st October 1999) - Witt, Christian; Borges, Adrian C; John, Mathias; Fietze, Ingo; Baumann, Gert; Krause, Andreas
Abstract : OBJECTIVE: The clinical course of fibrosing alveolitis (FA) in patients with systemic sclerosis (SSc) may vary considerably from stable condition for years to continuous fatal progression. This prospective study aimed at identifying the prognostic value of bronchoalveolar lavage fluid (BALF) analysis in FASSc. METHODS: Seventy three consecutive patients with SSc and clinical signs of pulmonary involvement were enrolled. Every patient underwent clinical examination, lung function tests, computed tomography (CT), gallium scan, echocardiography, and bronchoalveolar lavage (BAL). Forty nine patients, 26 with pathological and 23 with normal BALF findings were prospectively followed up for two years and re-evaluated annually. RESULTS: At baseline, 51 subjects (70%) showed radiological signs of lung fibrosis and/or alveolitis by CT and diffusion capacity for carbon monoxide (DLco) was decreased in 47 patients (64%). Thirty five patients (48%) had pathological BALF findings. BALF differential counts included BALF granulocytosis in 18, BALF lymphocytosis in 12, and a mixed increase of both granulocytes and lymphocytes in five patients. On follow up, a progression of FA with a significant decrease of DLco was only observed in patients with BALF granulocytosis. In contrast, patients with BALF lymphocytosis or normal BALF cell count had stable lung funtion parameters during the study period. In none of our patients echocardiography showed evidence of pulmonary hypertension. CONCLUSION: BALF granulocytosis predicts progression of FA with deterioration of lung function, which is most sensitively monitored by DLco. Immunosuppressive treatment is recommended in patients with granulocytic FASSc.